Manufacturing method for bonded magnet compound

By using specific thermosetting resins and hardeners in bond magnets, the proportion of reaction groups is controlled to form magnet alloys with high flowability and high filling rate, the problems of poor flowability and poor magnetic properties in the prior art are solved, and efficient magnet molding and excellent magnetic properties are achieved.

JP7667406B2Active Publication Date: 2025-04-23NICHIA CORP
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
JP2021008211
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-11-19
Filing Date
2021-01-21
Publication Date
2025-04-23
Estimated Expiration
2041-01-21

AI Technical Summary

Technical Problem

The prior art is difficult to improve the magnetic properties of bond magnets and the efficiency of filling magnetic powders, especially when using thermoplastic resins, poor fluidity and poor mold forming properties.

Method used

By adding a specific thermosetting resin and hardener between the thermoplastic resin and magnetic powder, the proportion of its reactive groups is controlled to form a magnet alloy with high flowability and high filling rate. The method includes thermal curing of the thermosetting resin with the hardener, eutectic with the magnetic powder and the thermoplastic resin, forming a bond magnet with improved magnetic properties.

Benefits of technology

The bond magnet is achieved with high flowability and high filling rate, which improves the magnetic properties and mold forming properties of the magnet, reduces the pressure during injection molding, and avoids the deterioration of magnet performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007667406000001
    Figure 0007667406000001
  • Figure 0007667406000002
    Figure 0007667406000002
Patent Text Reader

Abstract

To provide a compound for a bond magnet that can be highly filled with magnetic powder by improving the fluidity of a compound for a bond magnet containing a thermoplastic resin, and a bond magnet having improved magnetic characteristics.SOLUTION: A method for manufacturing a compound for a bond magnet includes a step of thermally hardening a thermosetting resin and a curing agent to obtain an additive for a bond magnet, the ratio of the number of reactive groups of the curing gent to the number of reactive groups of the thermosetting resin being 2 or more and 11 or less, and a kneading step of kneading the additive for a bond magnet, a magnetic powder, and a thermoplastic resin to obtain a compound for a bond magnet. The magnetic powder includes NdFeB-based magnetic powder and SmFeN-based anisotropic magnetic powder.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a compound for a bonded magnet. [Background technology]

[0002] Patent Document 1 discloses a method for producing a bonded magnet in which a thermoplastic resin and SmFeN particles are melt-kneaded, then compression-molded to produce a compound, which is then injection-molded.

[0003] On the other hand, Patent Document 2 discloses a bonded magnet that uses NdFeB magnetic powder, epoxy resin, and an amine-based hardener as a hardener for the epoxy resin. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2017-43804 A [Patent Document 2] JP 2010-232468 A Summary of the Invention [Problem to be solved by the invention]

[0005] The present invention aims to provide a bonded magnet compound containing a thermoplastic resin that has improved fluidity, thereby enabling high loading of magnetic powder, and a bonded magnet with improved magnetic properties. [Means for solving the problem]

[0006] A manufacturing method for a bonded magnet compound according to one embodiment of the present invention includes a step of thermally curing a thermosetting resin and a curing agent in which the ratio of the number of reactive groups to the number of reactive groups of the thermosetting resin is 2 or more and 11 or less to obtain an additive for a bonded magnet, and a kneading step of kneading the additive for a bonded magnet, a magnetic powder, and a thermoplastic resin to obtain a compound for a bonded magnet, the magnetic powder including a NdFeB magnetic powder and a SmFeN anisotropic magnetic powder.

[0007] A manufacturing method for a bonded magnet compound according to one embodiment of the present invention includes a step of thermally curing a thermosetting resin and a curing agent in which the ratio of the number of reactive groups to the number of reactive groups of the thermosetting resin is 2 or more and 11 or less to obtain an additive for the bonded magnet, a step of kneading the additive for the bonded magnet with a thermoplastic resin to obtain a resin composition for the bonded magnet, and a step of kneading the resin composition for the bonded magnet and a magnetic powder to obtain a compound for the bonded magnet, the magnetic powder including a NdFeB magnetic powder and a SmFeN anisotropic magnetic powder.

[0008] A method for producing a bonded magnet according to one embodiment of the present invention includes a step of thermally curing a thermosetting resin and a curing agent in which the ratio of the number of reactive groups to the number of reactive groups of the thermosetting resin is 2 or more and 11 or less to obtain an additive for a bonded magnet, a kneading step of kneading the additive for a bonded magnet, a magnetic powder, and a thermoplastic resin to obtain a compound for a bonded magnet, and an injection molding step of injection molding the compound for a bonded magnet, wherein the magnetic powder includes a NdFeB magnetic powder and a SmFeN anisotropic magnetic powder.

[0009] A method for producing a bonded magnet according to one embodiment of the present invention includes the steps of thermally curing a thermosetting resin and a curing agent in which the ratio of the number of reactive groups to the number of reactive groups of the thermosetting resin is 2 or more and 11 or less to obtain an additive for a bonded magnet, kneading the additive for a bonded magnet with a thermoplastic resin to obtain a resin composition for a bonded magnet, kneading the resin composition for a bonded magnet and a magnetic powder to obtain a compound for a bonded magnet, and injection molding the obtained compound for a bonded magnet, wherein the magnetic powder includes a NdFeB magnetic powder and a SmFeN anisotropic magnetic powder. Effect of the Invention

[0010] According to the above aspect, the flowability of the bonded magnet compound containing the thermoplastic resin can be improved, enabling a high filling rate of the magnetic powder, and providing a bonded magnet with improved magnetic properties. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] Hereinafter, the embodiments of the present invention will be described in detail. However, the embodiments shown below are examples for embodying the technical idea of ​​the present invention, and the present invention is not limited to the following. In this specification, the term "process" includes not only an independent process, but also a process that cannot be clearly distinguished from other processes as long as the intended purpose of the process is achieved.

[0012] The manufacturing method of the first bonded magnet compound of the present embodiment is as follows: A step of thermally curing a thermosetting resin and a curing agent having a ratio of the number of reactive groups to the number of reactive groups of the thermosetting resin of 2 or more and 11 or less to obtain an additive for bonded magnets; a kneading step of kneading the additive for bonded magnets, magnetic powder, and thermoplastic resin to obtain a compound for bonded magnets; Including, The magnetic powder contains NdFeB magnetic powder and SmFeN anisotropic magnetic powder.

[0013] When making a bonded magnet containing a thermoplastic resin, if a mixture of a thermoplastic resin and a thermosetting resin is injection molded, the reactive group of the thermosetting resin (for example, a glyceryl group in the case of an epoxy resin) reacts with the reactive group of the thermoplastic resin (for example, an amide group in the case of nylon 12), which may reduce the fluidity of the resin and deteriorate the moldability. In the cured product of the thermosetting resin of this embodiment and a curing agent whose equivalent ratio to the equivalent of the thermosetting resin is 2 to 11, the reactive group of the thermosetting resin is sufficiently deactivated by the reactive group of the curing agent (for example, an amino group in the case of DDS (diaminodiphenylsulfone)), so that the reaction with the reactive group of the thermoplastic resin is unlikely to occur and the decrease in the fluidity of the resin can be suppressed, and therefore it can be used as an additive for a bonded magnet containing a thermoplastic resin. In addition, when a bonded magnet is made by injection molding using a bonded magnet compound made with the additive for a bonded magnet containing a thermoplastic resin of this embodiment, the injection pressure can be reduced, and the magnetic properties of the obtained bonded magnet are improved.

[0014] The thermosetting resin is not particularly limited as long as it is thermosetting, and examples thereof include epoxy resin, phenol resin, urea resin, melamine resin, guanamine resin, unsaturated polyester resin, vinyl ester resin, diallyl phthalate resin, polyurethane resin, silicone resin, polyimide resin, alkyd resin, furan resin, dicyclopentadiene resin, acrylic resin, and allyl carbonate resin. Among them, epoxy resin is preferred in terms of mechanical properties and heat resistance. The thermosetting resin is preferably a liquid at room temperature or a solid that dissolves in a solvent and becomes liquid. In addition, in the case of epoxy resin, it is preferable to select one that has a rigid skeleton and a crystal structure with little steric hindrance, has a small molecular weight, and has high fluidity in terms of reactivity with the curing agent, and examples thereof include biphenyl type, bisphenol A type, naphthalene type, and anthracene type. Examples of the epoxy resin that can be used include jER-YX4000, jER-828, jER-YX8800, jER-YL6121HA, jER-YL6677 (manufactured by Mitsubishi Chemical Corporation), EPICLON-HP-4032D, HP-7200L, HP-7200, HP-7200H, HP-7200HH, HP-7200HHH, HP-4700, HP-4770, HP-5000, HP-6000, HP-4710 (manufactured by DIC Corporation), YDC-1312, YSLV-70XY, and YSLV-80XY (manufactured by Nippon Steel Chemical & Material Co., Ltd.).

[0015] The curing agent is not particularly limited as long as it can thermally cure the selected thermosetting resin, and when the thermosetting resin is an epoxy resin, examples of the curing agent include amine-based curing agents, acid anhydride-based curing agents, polyamide-based curing agents, imidazole-based curing agents, phenolic resin-based curing agents, polymercaptan resin-based curing agents, polysulfide resin-based curing agents, organic acid hydrazide-based curing agents, etc. Examples of the amine-based curing agents include diaminodiphenylsulfone, metaphenylenediamine, diaminodiphenylmethane, diethylenetriamine, triethylenetetramine, etc.

[0016] When nylon resin is used as the thermoplastic resin and epoxy resin is used as the thermosetting resin, it is preferable to use a diamine-based curing agent having an aromatic skeleton. The diamine-based curing agent having an aromatic skeleton has a chemical structure with less steric hindrance around the amino group, which is a reactive group, due to the aromatic skeleton, and therefore has good reactivity with the glycidyl group, which is a reactive group of the epoxy resin, and the amino group has high affinity with the amide group, which is a reactive group of the nylon resin, which is thought to improve the fluidity of the nylon resin. Examples of such curing agents include, in addition to the above-mentioned diaminodiphenylsulfone, metaphenylenediamine, and diaminodiphenylmethane, 9,9-bis(4-amino-3-methylphenyl)fluorene, bisaniline P, bisaniline M, benzoguanamine, 3,3'-dinitrobenzidine, 4,4'-methylenebis(2-ethyl-6-methylaniline), o-tolidine, bis[4-(4-aminophenoxy)phenyl]sulfone, bis[4-(3-aminophenoxy)phenyl]sulfone, 1,3-phenylenediamine, 2,2'-bis(trifluoromethyl)benzidine, 4,4'-diaminodiphenylmethane, 3,3'-sulfonyldianiline, 4,4'-diaminodiphenyl ether, and 1,3-bis(3-aminophenoxy)benzene.

[0017] The amount of the curing agent is adjusted by the ratio of the number of reactive groups to the number of reactive groups of the thermosetting resin (the ratio of the equivalent of the curing agent to the equivalent of the thermosetting resin). The ratio of the number of reactive groups of the curing agent to the number of reactive groups of the thermosetting resin is 2 or more and 11 or less, preferably 2 or more and 10 or less, and more preferably 2 or more and 7 or less. The lower limit of the number of reactive groups is preferably more than 2.5, more preferably 3 or more. If the ratio exceeds 11, the mechanical properties of the bonded magnet are reduced, and if it is less than 2, the ratio of the reactive groups of the curing agent to the reactive groups of the thermosetting resin is small, so that the reactive groups of the thermosetting resin remain. When kneaded with the thermoplastic resin in the subsequent process, the reactive groups of the thermoplastic resin react with the remaining reactive groups of the thermosetting resin, causing an increase in viscosity during injection molding, and the moldability of the bonded magnet and the mechanical properties of the obtained molded product are worse than those of the thermoplastic resin alone. Here, the equivalent of a thermosetting resin species refers to the number of grams of resin containing 1 gram equivalent of reactive groups, and the equivalent of a hardener species refers to the active hydrogen equivalent.

[0018] The cured product can be obtained by mixing the above-mentioned thermosetting resin with a curing agent and thermally curing the mixture. The temperature for thermal curing can be set according to the characteristics of the thermosetting resin used, but from the viewpoint of curing properties, it is preferably 60°C or higher and 250°C or lower, more preferably 180°C or higher and 220°C or lower.

[0019] The cured product can be pulverized as necessary. The method for pulverizing the cured product is not particularly limited, and a sample mill, a ball mill, a stamp mill, a mortar, a mixer pulverization, or the like can be used. If necessary, the pulverized product can be classified using a sieve or the like. The average particle size of the pulverized product is preferably 1000 μm or less, more preferably 500 μm or less, from the viewpoint of compatibility with the thermoplastic resin.

[0020] The additive for bonded magnets can also be obtained by mixing a curing accelerator with a thermosetting resin and a curing agent and curing the mixture. Examples of the curing accelerator include 1,8-diazabicyclo(5,4,0)-undecene-7, 1,5-diazabicyclo(4,3,0)-nonene-5, 1-cyanoethyl-2-ethyl-4-methylimidazole, 2-methyl-4-methylimidazole, triphenylphosphine, and sulfonium salts. The amount of the curing accelerator is not particularly limited, but is generally added in an amount of 0.01% by mass or more and 10% by mass or less based on the total amount of the thermosetting resin and the curing agent.

[0021] In the kneading process, the bond magnet additive, the magnetic powder, and the thermoplastic resin are melt-kneaded to prepare a bond magnet compound to be used in injection molding. The melt kneader is not particularly limited, but a single screw kneader, a twin screw kneader, a mixing roll, a kneader, a Banbury mixer, an intermeshing twin screw extruder, a non-intermeshing twin screw extruder, etc. can be used. The melt kneading temperature is not particularly limited and can be set according to the characteristics of the thermoplastic resin used, but it is preferably 180°C or higher and 250°C or lower.

[0022] The thermoplastic resin is not particularly limited as long as it is an injection moldable resin, and examples thereof include nylon resin (polyamide), polyolefins such as polypropylene (PP) and polyethylene (PE), polyester, polycarbonate (PC), polyphenylene sulfide (PPS), polyether ether ketone (PEEK), polyacetal (POM), liquid crystal polymer (LCP), etc. Examples of the nylon resin include polylactams such as nylon 6, nylon 11, and nylon 12, condensates of dicarboxylic acid and diamine such as nylon 6,6, nylon 6,10, and nylon 6,12, copolymer polyamides such as nylon 6 / 6,6, nylon 6 / 6,10, nylon 6 / 12, nylon 6 / 6,12, nylon 6 / 6,10 / 6,10, nylon 6 / 6,6 / 6,12, and nylon 6 / polyether, nylon 6T, nylon 9T, nylon MXD6, aromatic nylon, and amorphous nylon. Among these, nylon resin is preferred, and nylon 12 is particularly preferred, because of its low water absorption rate, moldability, and mechanical properties.

[0023] The magnetic powder includes NdFeB magnetic powder and SmFeN anisotropic magnetic powder. The SmFeN anisotropic magnetic powder is Th2Zn 17 It has a crystal structure of the type Sm x Fe 100-x-y N y It is a nitride consisting of rare earth metal samarium Sm, iron Fe, and nitrogen N, represented by the formula: Here, x is preferably 8.1 atomic % or more and 10 atomic % or less, y is preferably 13.5 atomic % or more and 13.9 atomic % or less, and the remainder is mainly Fe, and the particle size distribution is preferably monodisperse from the viewpoint of the squareness of the demagnetization characteristics. The SmFeN-based anisotropic magnetic powder can be produced by the method disclosed in JP-A-11-189811.

[0024] The NdFeB magnetic powder can be produced by the HDDR method disclosed in International Publication No. 2003 / 85147. The average particle size of the NdFeB magnetic powder is preferably 40 μm or more and 200 μm or less.

[0025] The magnetic powder may further contain SmCo magnetic powder in addition to the NdFeB magnetic powder and the SmFeN anisotropic magnetic powder. The SmCo magnetic powder can be produced by the method disclosed in JP-A-08-260083, and preferably has an average diameter of 10 μm to 30 μm.

[0026] The magnetic powder may be phosphoric acid treated as necessary. The phosphoric acid treatment liquid is basically dissolved in water or an organic solvent such as isopropanol, and the magnetic powder is put into a phosphoric acid bath to which a reaction accelerator such as nitrate ions and a crystal refiner such as V ions, Cr ions, and Mo ions are added as necessary, to form a passivation film having a PO bond on the surface of the rare earth magnetic powder. Examples of the phosphoric acid treatment agent include inorganic phosphoric acids and organic phosphoric acids such as orthophosphoric acid, sodium dihydrogen phosphate, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, zinc phosphate, and calcium phosphate, hypophosphorous acid, hypophosphite, pyrophosphoric acid, and polyphosphoric acid.

[0027] [Silica treatment process] The magnetic powder may be silica-treated as necessary. The oxidation resistance can be improved by forming a thin silica film on the magnetic powder. The thin silica film can be formed, for example, by mixing an alkyl silicate, a phosphate-coated magnetic powder, and an alkaline solution.

[0028] [Silane coupling treatment process] The magnetic powder after silica treatment may be further treated with a silane coupling agent. By subjecting the magnetic powder on which the silica thin film has been formed to a silane coupling treatment, a coupling agent film is formed on the silica thin film, improving the magnetic properties of the magnetic powder, as well as improving the wettability with resin and the strength of the magnet.The silane coupling agent is not particularly limited and may be selected according to the type of resin. Examples of the silane coupling agent include 3-aminopropyltriethoxysilane, γ-(2-aminoethyl)aminopropyltrimethoxysilane, γ-(2-aminoethyl)aminopropylmethyldimethoxysilane, γ-methacryloxypropyltrimethoxysilane, γ-methacryloxypropylmethyldimethoxysilane, N-β-(N-vinylbenzylaminoethyl)-γ-aminopropyltrimethoxysilane hydrochloride, γ-glycidoxypropyltrimethoxysilane, γ-mercaptopropyltrimethoxysilane, and the like. Captopropyltrimethoxysilane, methyltrimethoxysilane, methyltriethoxysilane, vinyltriacetoxysilane, γ-chloropropyltrimethoxysilane, hexamethylenedisilazane, γ-anilinopropyltrimethoxysilane, vinyltrimethoxysilane, octadecyl[3-(trimethoxysilyl)propyl]ammonium chloride, γ-chloropropylmethyldimethoxysilane, γ-mercaptopropylmethyldimethoxysilane, methyltrichlorosilane, dimethyldichlorosilane, trimethylchlorosilane, vinyl Trichlorosilane, vinyltris(β-methoxyethoxy)silane, vinyltriethoxysilane, β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, γ-glycidoxypropylmethyldiethoxysilane, N-β(aminoethyl)γ-aminopropyltrimethoxysilane, N-β(aminoethyl)γ-aminopropylmethyldimethoxysilane, γ-aminopropyltriethoxysilane, N-phenyl-γ-aminopropyltrimethoxysilane, oleopropyltriethoxysilane, γ-isocyanatopropyltriethoxysilane Examples of silane coupling agents include silane, polyethoxydimethylsiloxane, polyethoxymethylsiloxane, bis(trimethoxysilylpropyl)amine, bis(3-triethoxysilylpropyl)tetrasulfane, γ-isocyanatepropyltrimethoxysilane, vinylmethyldimethoxysilane, 1,3,5-N-tris(3-trimethoxysilylpropyl)isocyanurate, t-butylcarbamatetrialkoxysilane, and N-(1,3-dimethylbutylidene)-3-(triethoxysilyl)-1-propaneamine.These silane coupling agents may be used alone or in combination of two or more. The amount of the silane coupling agent added is preferably 0.2 parts by weight or more and 0.8 parts by weight or less, more preferably 0.25 parts by weight or more and 0.6 parts by weight or less, relative to 100 parts by weight of the magnetic powder. If the amount is less than 0.2 parts by weight, the effect of the silane coupling agent is small, and if the amount is more than 0.8 parts by weight, the magnetic powder tends to aggregate, which reduces the magnetic properties of the magnetic powder and magnet.

[0029] The magnetic powder after the silica treatment or silane coupling treatment can be filtered, dehydrated and dried by a conventional method.

[0030] In the first method for producing a bonded magnet compound of this embodiment, the filling rate of the magnetic powder in the bonded magnet compound is preferably 75% by mass or more and 96% by mass or less, and more preferably 90% by mass or more and 95.5% by mass or less. If it exceeds 96% by mass, the viscosity during injection molding increases, resulting in reduced moldability, and if it is less than 75% by mass, the residual magnetic flux density of the bonded magnet will be low.

[0031] In the manufacturing method of the first bonded magnet compound of this embodiment, the mass ratio of the NdFeB magnetic powder to the SmFeN anisotropic magnetic powder may be, for example, 0.05 to 5, preferably 0.1 to 4.5, and more preferably 0.2 to 4. If it is less than 0.05, the viscosity during injection molding increases, resulting in reduced moldability, and if it is more than 5, the residual magnetic flux density decreases.

[0032] The content of the additive for bonded magnets in the first bonded magnet compound of this embodiment is preferably 0.1% by mass to 4.2% by mass, more preferably 0.3% by mass to 3.5% by mass, and even more preferably 0.5% by mass to 1.2% by mass. If the content of the additive for bonded magnets exceeds 4.2% by mass, the residual magnetic flux density of the bonded magnet decreases, and if it is less than 0.1% by mass, the viscosity during injection molding increases, resulting in reduced moldability.

[0033] The content of the thermoplastic resin in the first bonded magnet compound of this embodiment is preferably 2.5% by mass to 25% by mass, more preferably 3.5% by mass to 10% by mass. If the content of the thermoplastic resin exceeds 25% by mass, the residual magnetic flux density of the bonded magnet decreases, and if it is less than 2.5% by mass, the viscosity during injection molding increases, reducing moldability.

[0034] In the first bonded magnet compound of this embodiment, the weight parts of the bonded magnet additive per 100 weight parts of magnetic powder is preferably 0.1 to 5.6 parts by weight, more preferably 0.31 to 4.67 parts by weight, and even more preferably 0.52 to 1.6 parts by weight. If the bonded magnet additive exceeds 5.6 parts by weight, the residual magnetic flux density of the bonded magnet will be low, and if it is less than 0.1 part by weight, the viscosity during injection molding will be high, resulting in poor moldability.

[0035] In the first bonded magnet compound of this embodiment, the weight parts of thermoplastic resin per 100 weight parts of magnetic powder is preferably 2.6 to 33 parts by weight, more preferably 3.6 to 14 parts by weight. If the weight parts of thermoplastic resin exceed 33 parts by weight, the residual magnetic flux density of the bonded magnet will be low, and if it is less than 2.6 parts by weight, the viscosity during injection molding will be high, resulting in poor moldability.

[0036] The manufacturing method of the second bonded magnet compound of the present embodiment is as follows: A step of thermally curing a thermosetting resin and a curing agent having a ratio of the number of reactive groups to the number of reactive groups of the thermosetting resin of 2 or more and 11 or less to obtain an additive for bonded magnets; A step of kneading the additive for bonded magnets with a thermoplastic resin to obtain a resin composition for bonded magnets; a kneading step of kneading the resin composition for bonded magnets and magnetic powder to obtain a compound for bonded magnets; Including, The magnetic powder contains NdFeB magnetic powder and SmFeN anisotropic magnetic powder.

[0037] The process for obtaining the additive for bonded magnets, and the thermosetting resin, curing agent, and magnetic powder used in this process are as described above.

[0038] The kneading process for obtaining the resin composition for bonded magnets and the thermoplastic resin used in the process are as described above. A molten mixture is obtained by melt-kneading a thermosetting resin and a cured product of a curing agent in which the ratio of the number of reactive groups to the number of reactive groups of the thermosetting resin is 2 to 11, and a thermoplastic resin before kneading with a magnetic powder. In the obtained kneaded product, the thermoplastic resin and the cured product may be completely compatible, partially compatible, or incompatible as long as they have been melt-kneaded in advance, but completely compatible is preferable.

[0039] In the resin composition for bonded magnets obtained by thoroughly kneading the cured product and the thermoplastic resin, if the thermoplastic resin is a crystalline resin, the melting point and crystallization temperature are lowered. As a result, the injection pressure of the compound for bonded magnets is also reduced, and the orientation rate and magnetic properties of the obtained bonded magnet are improved. The melting point is preferably 3.0°C or more lower than the melting point of the thermoplastic resin, and more preferably 4.5°C or more lower. The crystallization temperature is preferably 2.0°C or more lower than the crystallization temperature of the thermoplastic resin, and more preferably 3.0°C or more lower.

[0040] When polyamide 12 is used as the thermoplastic resin, the melting point (peak top) of the resin composition for bonded magnets is preferably 160° C. or higher and 177° C. or lower, more preferably 170° C. or higher and 175° C. or lower. The difference between the peak top of the melting peak and the final melting point is preferably more than 5.0° C., more preferably more than 5.5° C. Furthermore, the heat quantity of the melting peak is preferably 50 mJ / mg or higher, more preferably 55 mJ / mg or higher.

[0041] The amount of the additive for bonded magnets in the resin composition consisting of the additive for bonded magnets and the thermoplastic resin is preferably 5% by mass to 50% by mass, more preferably 10% by mass to 20% by mass. If it exceeds 50% by mass, the filling rate of the magnetic powder decreases, and if it is less than 5% by mass, the effect of lowering the melting point and crystallization temperature of the molten mixture is small, and the injection pressure during molding of the bonded magnet cannot be sufficiently reduced.

[0042] The process for obtaining a compound for a bonded magnet and the magnetic powder used in this process are as described above.

[0043] In the second method for producing a bonded magnet compound of this embodiment, the filling rate of the magnetic powder in the bonded magnet compound is preferably 75% by mass or more and 96% by mass or less, and more preferably 90% by mass or more and 95.5% by mass or less. If it exceeds 96% by mass, the viscosity during injection molding increases, resulting in reduced moldability, and if it is less than 75% by mass, the residual magnetic flux density of the bonded magnet will be low.

[0044] In the manufacturing method of the second bonded magnet compound of this embodiment, the mass ratio of the NdFeB magnetic powder to the SmFeN anisotropic magnetic powder may be, for example, 0.05 to 5, preferably 0.1 to 4.5, and more preferably 0.2 to 4. If it is less than 0.05, the viscosity during injection molding increases, resulting in reduced moldability, and if it is more than 5, the residual magnetic flux density decreases.

[0045] The content of the resin composition for bonded magnets in the second bonded magnet compound of this embodiment is preferably 2.5% by mass to 25% by mass, more preferably 3.5% by mass to 10% by mass. If the content of the resin composition for bonded magnets exceeds 25% by mass, the residual magnetic flux density of the bonded magnet decreases, and if it is less than 2.5% by mass, the viscosity during injection molding increases, resulting in reduced moldability.

[0046] In the second bonded magnet compound of this embodiment, the parts by weight of the resin composition for bonded magnets per 100 parts by weight of the magnetic powder is preferably 2.6 parts by weight or more and 33 parts by weight or less, and more preferably 3.6 parts by weight or more and 14 parts by weight or less. If the parts by weight of the resin composition for bonded magnets exceeds 33 parts by weight, the residual magnetic flux density of the bonded magnet will be low, and if it is less than 2.6 parts by weight, the viscosity during injection molding will be high, resulting in poor moldability.

[0047] The compound for bonded magnets of this embodiment is obtained by the manufacturing method described above.

[0048] The manufacturing method of the first bonded magnet of the present embodiment is as follows: A step of thermally curing a thermosetting resin and a curing agent having a ratio of the number of reactive groups to the number of reactive groups of the thermosetting resin of 2 to 11 to obtain an additive for bonded magnets; a kneading step of kneading the bonded magnet additive, magnetic powder, and thermoplastic resin to obtain a bonded magnet compound; an injection molding process for injection molding the obtained bonded magnet compound; Including, The magnetic powder contains NdFeB magnetic powder and SmFeN anisotropic magnetic powder.

[0049] The method for producing the second bonded magnet of the present embodiment is as follows: A step of thermally curing a thermosetting resin and a curing agent having a ratio of the number of reactive groups to the number of reactive groups of the thermosetting resin of 2 to 11 to obtain an additive for bonded magnets; A step of kneading the additive for bonded magnets with a thermoplastic resin to obtain a resin composition for bonded magnets; a kneading step of kneading the resin composition for bonded magnets and magnetic powder to obtain a compound for bonded magnets; an injection molding process for injection molding the obtained bonded magnet compound; Including, The magnetic powder contains NdFeB magnetic powder and SmFeN anisotropic magnetic powder.

[0050] In these two methods for producing bonded magnets, the process for obtaining the additive for bonded magnets and the kneading process for obtaining the compound for bonded magnets are as described above.

[0051] In the injection molding process, the bond magnet compound is injection molded to obtain an injection molded product. The cylinder temperature of the injection molding machine may be within the temperature range in which the bond magnet compound melts, and is preferably 280°C or less in order to suppress magnetic deterioration of the magnetic powder due to heat. The injection pressure may be any pressure that allows the molten compound to be injected, but for example, when the cylinder temperature of the injection molding machine is 260°C and injection molding is performed into a cavity with a diameter of 10 mm and a thickness of 7 mm, it is preferable that the cavity can be completely filled at less than 250 MPa in terms of moldability.

[0052] The first bonded magnet of this embodiment is obtained, for example, by the manufacturing method of the first bonded magnet of this embodiment described above, and is characterized by including a bonded magnet additive, a magnetic powder, and a thermoplastic resin. The first bonded magnet is manufactured at a low injection pressure by using a bonded magnet compound with high fluidity that includes a bonded magnet additive, so that the magnetic deterioration of the magnetic powder due to injection molding is suppressed, and the magnetic properties of the bonded magnet are improved.

[0053] In the first bonded magnet of this embodiment, the filling rate of the magnetic powder in the bonded magnet is preferably 75% by mass to 96% by mass, and more preferably 90% by mass to 95.5% by mass. If it exceeds 96% by mass, the viscosity during injection molding increases, decreasing moldability, and if it is less than 75% by mass, the residual magnetic flux density of the bonded magnet decreases.

[0054] In the first bonded magnet of this embodiment, the mass ratio of the NdFeB magnetic powder to the SmFeN anisotropic magnetic powder may be, for example, 0.05 to 5, preferably 0.1 to 4.5, and more preferably 0.2 to 4. If it is less than 0.05, the viscosity during injection molding increases, resulting in reduced moldability, and if it is more than 5, the residual magnetic flux density decreases.

[0055] In the first bonded magnet of this embodiment, the content of the additive for bonded magnets in the bonded magnet is preferably 0.1% by mass to 4.2% by mass, more preferably 0.3% by mass to 3.5% by mass, and even more preferably 0.5% by mass to 1.2% by mass. If the content of the additive for bonded magnets exceeds 4.2% by mass, the residual magnetic flux density of the bonded magnet decreases, and if it is less than 0.1% by mass, the viscosity during injection molding increases, reducing moldability.

[0056] In the first bonded magnet of this embodiment, the content of the thermoplastic resin in the bonded magnet is preferably 2.5% by mass to 25% by mass, and more preferably 3.5% by mass to 10% by mass. If the content of the thermoplastic resin exceeds 25% by mass, the residual magnetic flux density of the bonded magnet decreases, and if it is less than 2.5% by mass, the viscosity during injection molding increases, resulting in reduced moldability.

[0057] In the first bonded magnet of this embodiment, the weight parts of the additive for bonded magnets per 100 parts by weight of magnetic powder is preferably 0.1 to 5.6 parts by weight, more preferably 0.31 to 4.67 parts by weight, and even more preferably 0.52 to 1.6 parts by weight. If the additive for bonded magnets exceeds 5.6 parts by weight, the residual magnetic flux density of the bonded magnet will be low, and if it is less than 0.1 part by weight, the viscosity during injection molding will be high, resulting in poor moldability.

[0058] In the first bonded magnet of this embodiment, the weight parts of the thermoplastic resin per 100 weight parts of the magnetic powder is preferably 2.6 to 33 parts by weight, more preferably 3.6 to 14 parts by weight. If the weight parts of the thermoplastic resin exceed 33 parts by weight, the residual magnetic flux density of the bonded magnet will be low, and if it is less than 2.6 parts by weight, the viscosity during injection molding will be high, resulting in poor moldability.

[0059] The orientation rate in the first bonded magnet of the present embodiment is not particularly limited, but is preferably 98.3% or more, and more preferably 99% or more.

[0060] The residual magnetic flux density of the first bonded magnet of this embodiment is not particularly limited, but is preferably at least 0.8 T, and more preferably at least 0.9 T. By using the resin additive for bonded magnets of this embodiment, a high residual magnetic flux density can be achieved.

[0061] The coercive force of the first bonded magnet of this embodiment is not particularly limited, but is preferably 1000 kA / m or more. By using the resin additive for bonded magnets of this embodiment, a high coercive force can be achieved.

[0062] The first bonded magnet of this embodiment is produced by kneading a bonded magnet additive, a magnetic powder, and a thermoplastic resin, so that the bonded magnet additive and the magnetic powder each exist independently.

[0063] The second bonded magnet of this embodiment is obtained, for example, by the manufacturing method of the second bonded magnet of this embodiment described above, and is characterized by including a resin composition for bonded magnets and magnetic powder. The second bonded magnet is produced at low injection pressure by using a highly fluid compound for bonded magnets that includes the resin composition for bonded magnets, so that magnetic deterioration of the magnetic powder due to injection molding is suppressed, and the magnetic properties of the bonded magnet are improved.

[0064] In the second bonded magnet of this embodiment, the filling rate of the magnetic powder in the bonded magnet is preferably 75% by mass to 96% by mass, and more preferably 90% by mass to 95.5% by mass. If it exceeds 96% by mass, the viscosity during injection molding increases, reducing moldability, and if it is less than 75% by mass, the residual magnetic flux density of the bonded magnet decreases.

[0065] In the second bonded magnet of this embodiment, the mass ratio of the NdFeB magnetic powder to the SmFeN anisotropic magnetic powder may be, for example, from 0.05 to 5, preferably from 0.1 to 4.5, and more preferably from 0.2 to 4. If it is less than 0.05, the viscosity during injection molding increases, reducing moldability, and if it is more than 5, the residual magnetic flux density decreases.

[0066] In the second bonded magnet of this embodiment, the content of the resin composition for bonded magnets in the bonded magnet is preferably 2.5% by mass to 25% by mass, more preferably 3.5% by mass to 10% by mass. If the content of the resin composition for bonded magnets exceeds 25% by mass, the residual magnetic flux density of the bonded magnet decreases, and if it is less than 2.5% by mass, the viscosity during injection molding increases, resulting in reduced moldability.

[0067] In the second bonded magnet of this embodiment, the weight parts of the resin composition for bonded magnets per 100 weight parts of magnetic powder is preferably 2.6 to 33 parts by weight, more preferably 3.6 to 14 parts by weight. If the weight parts of the resin composition for bonded magnets exceeds 33 parts by weight, the residual magnetic flux density of the bonded magnet will be low, and if it is less than 2.6 parts by weight, the viscosity during injection molding will be high, resulting in poor moldability.

[0068] The orientation rate in the second bonded magnet of this embodiment is not particularly limited, but is preferably 98.3% or more, and more preferably 99% or more.

[0069] The residual magnetic flux density in the second bonded magnet of this embodiment is not particularly limited, but is preferably at least 0.8 T, and more preferably at least 0.9 T. By using the resin composition for bonded magnets of this embodiment, which contains a cured product of a thermosetting resin and a curing agent, and a melt-kneaded product of a thermoplastic resin, a high residual magnetic flux density can be achieved.

[0070] The coercive force of the second bonded magnet of this embodiment is not particularly limited, but is preferably 1000 kA / m or more. By using the resin composition for bonded magnets of this embodiment, which contains a cured product of a thermosetting resin and a curing agent, and a melt-kneaded product of a thermoplastic resin, a high coercive force can be achieved.

[0071] The second bonded magnet of the present embodiment is produced by kneading the resin composition for bonded magnets and the magnetic powder, so that the resin composition for bonded magnets and the magnetic powder each exist independently.

[0072] <SmFeN-based anisotropic magnetic powder> In the method for producing the compounds for the first and second bonded magnets of the present embodiment, the SmFeN-based anisotropic magnetic powder contained in the magnetic powder is not particularly limited. For example, a step of mixing a solution containing Sm and Fe with a precipitating agent to obtain a precipitate containing Sm and Fe (precipitation step), a step of firing the precipitate to obtain an oxide containing Sm and Fe (oxidation step), a step of heat-treating the oxide in an atmosphere containing a reducing gas to obtain a partial oxide (pretreatment step), a step of reducing the partial oxide (reduction step), and a step of nitriding the alloy particles obtained in the reduction step (nitriding step) Those produced by a method including can be preferably used.

[0073] [Precipitation step] In the precipitation step, a Sm raw material and an Fe raw material are dissolved in a strongly acidic solution to prepare a solution containing Sm and Fe. When obtaining Sm2Fe 17 N3 as the main phase, the molar ratio of Sm and Fe (Sm:Fe) is preferably 1.5:17 to 3.0:17, more preferably 2.0:17 to 2.5:17. Raw materials such as La, W, Co, Ti, Sc, Y, Pr, Nd, Pm, Gd, Tb, Dy, Ho, Er, Tm, and Lu may be added to the aforementioned solution.

[0074] The Sm raw material and the Fe raw material are not limited as long as they can be dissolved in a strongly acidic solution. For example, in terms of availability, samarium oxide can be used as the Sm raw material, and FeSO4 can be used as the Fe raw material. The concentration of the solution containing Sm and Fe can be appropriately adjusted within the range where the Sm raw material and the Fe raw material are substantially dissolved in the acidic solution. Sulfuric acid can be mentioned as the acidic solution in terms of solubility.

[0075] By reacting the solution containing Sm and Fe with a precipitant, an insoluble precipitate containing Sm and Fe is obtained. Here, the solution containing Sm and Fe may be a solution containing Sm and Fe when reacted with the precipitant. For example, raw materials containing Sm and Fe may be prepared as separate solutions, and each solution may be dropped to react with the precipitant. Even when preparing them as separate solutions, each raw material is appropriately adjusted to a range in which it is substantially soluble in the acidic solution. The precipitant is not limited as long as it is an alkaline solution that reacts with the solution containing Sm and Fe to obtain a precipitate, and examples of the precipitant include ammonia water and caustic soda, with caustic soda being preferred.

[0076] The precipitation reaction is preferably carried out by dropping a solution containing Sm and Fe and a precipitant into a solvent such as water, from the viewpoint of easily adjusting the properties of the precipitate particles. By appropriately controlling the supply rate of the solution containing Sm and Fe and the precipitant, the reaction temperature, the concentration of the reaction solution, the pH during the reaction, etc., a precipitate having a uniform distribution of the constituent elements, a sharp particle size distribution, and a regular powder shape can be obtained. By using such a precipitate, the magnetic properties of the magnetic powder, which is the final product, are improved. The reaction temperature can be set to 0 to 50°C, and is preferably 35 to 45°C. The reaction solution concentration is preferably 0.65 mol / L to 0.85 mol / L, and more preferably 0.7 mol / L to 0.84 mol / L, as the total concentration of metal ions. The reaction pH is preferably 5 to 9, and more preferably 6.5 to 8.

[0077] The anisotropic magnetic powder particles obtained in the precipitation process roughly determine the powder particle size, powder shape, and particle size distribution of the finally obtained magnetic powder. When the particle size of the obtained particles is measured by a laser diffraction type wet particle size distribution meter, it is preferable that the size and distribution of the whole powder is almost within the range of 0.05 to 20 μm, preferably 0.1 to 10 μm. In addition, the average particle size of the anisotropic magnetic powder particles is measured as the particle size equivalent to 50% of the cumulative volume from the small particle size side in the particle size distribution, and is preferably within the range of 0.1 to 10 μm.

[0078] After separating the precipitate, it is preferable to remove the solvent from the separated material in order to prevent the precipitate from redissolving in the remaining solvent in the heat treatment of the subsequent oxidation step, and the precipitate from agglomerating when the solvent evaporates, or from changing the particle size distribution, powder particle size, etc. Specific examples of the method for removing the solvent include drying in an oven at 70 to 200°C for 5 to 12 hours when water is used as the solvent.

[0079] After the precipitation step, a step of separating and washing the resulting precipitate may be included. The washing step is carried out so that the conductivity of the supernatant solution is 5 mS / m 2 The process is appropriately continued until the following is reached: In the step of separating the precipitate, for example, a solvent (preferably water) can be added to the obtained precipitate and mixed, followed by filtration, decantation, or the like.

[0080] [Oxidation process] The oxidation step is a step of obtaining an oxide containing Sm and Fe by firing the precipitate formed in the precipitation step. For example, the precipitate can be converted into an oxide by heat treatment. When the precipitate is heat treated, it must be performed in the presence of oxygen, for example, in an air atmosphere. In addition, since it must be performed in the presence of oxygen, it is preferable that the nonmetallic part in the precipitate contains oxygen atoms.

[0081] The heat treatment temperature in the oxidation step (hereinafter, oxidation temperature) is not particularly limited, but is preferably 700 to 1300° C., and more preferably 900 to 1200° C. If the temperature is less than 700° C., the oxidation is insufficient, and if the temperature exceeds 1300° C., the desired shape, average particle size, and particle size distribution of the magnetic powder tend not to be obtained. The heat treatment time is also not particularly limited, but is preferably 1 to 3 hours.

[0082] The oxide particles obtained have sufficient microscopic mixing of Sm and Fe within the oxide particles, and are oxide particles that reflect the shape, particle size distribution, etc. of the precipitate.

[0083] [Pretreatment process] The pretreatment step is a step in which an oxide containing Sm and Fe is heat-treated in a reducing gas atmosphere to obtain a partial oxide in which a part of the oxide is reduced.

[0084] Here, the partial oxide refers to an oxide in which a part of the oxide is reduced. The oxygen concentration of the oxide is not particularly limited, but is preferably 10% by mass or less, and more preferably 8% by mass or less. If it exceeds 10% by mass, the reduction heat generated by reduction with Ca becomes large in the reduction step, and the firing temperature becomes high, which tends to result in particles with abnormal particle growth. Here, the oxygen concentration of the partial oxide can be measured by non-dispersive infrared absorption method (ND-IR).

[0085] The reducing gas is appropriately selected from hydrocarbon gases such as hydrogen (H2), carbon monoxide (CO), and methane (CH4), but hydrogen gas is preferred from the viewpoint of cost, and the flow rate of the gas is appropriately adjusted within a range in which oxides do not fly off. The heat treatment temperature in the pretreatment step (hereinafter, pretreatment temperature) is in the range of 300°C to 950°C, preferably 400°C or higher, more preferably 750°C or higher, and preferably less than 900°C. When the pretreatment temperature is 300°C or higher, the reduction of oxides containing Sm and Fe proceeds efficiently. Furthermore, when the pretreatment temperature is 950°C or lower, particle growth and segregation of oxide particles are suppressed, and the desired particle size can be maintained. Furthermore, when hydrogen is used as the reducing gas, it is preferable to adjust the thickness of the oxide layer used to 20 mm or less, and further adjust the dew point in the reactor to -10°C or less.

[0086] [Reduction process] The reduction step is a step of obtaining alloy particles by heat treating the partial oxide in the presence of a reducing agent at 920°C to 1200°C, for example, by contacting the partial oxide with calcium melt or calcium vapor. From the viewpoint of magnetic properties, the heat treatment temperature is preferably 950°C to 1150°C, more preferably 980°C to 1100°C. From the viewpoint of carrying out the reduction reaction more uniformly, the heat treatment time is preferably less than 120 minutes, more preferably less than 90 minutes, and the lower limit of the heat treatment time is preferably 10 minutes or more, more preferably 30 minutes or more.

[0087] Metallic calcium is used in the form of granules or powder, and the particle size is preferably 10 mm or less. This makes it possible to more effectively suppress aggregation during the reduction reaction. Metallic calcium can be added in an amount of 1.1 to 3.0 times the reaction equivalent (the stoichiometric amount required to reduce Sm oxide, and if Fe is in the form of oxide, includes the amount required to reduce it), and preferably 1.5 to 2.0 times.

[0088] In the reduction step, a disintegration promoter can be used as necessary together with metallic calcium as a reducing agent. The disintegration promoter is used as appropriate to promote disintegration and granulation of the product in the water washing step described below, and examples of the disintegration promoter include alkaline earth metal salts such as calcium chloride and alkaline earth oxides such as calcium oxide. These disintegration promoters are used in a ratio of 1 to 30% by mass, preferably 5 to 28% by mass, based on the Sm oxide used as the Sm source.

[0089] [Nitriding process] The nitriding process is a process for obtaining anisotropic magnetic particles by nitriding the alloy particles obtained in the reduction process. Since the particulate precipitate obtained in the precipitation process is used, the alloy particles in the form of porous aggregates are obtained in the reduction process. This allows the alloy particles to be heat-treated and nitrided immediately in a nitrogen atmosphere without the need for a pulverization process, so that the nitriding can be performed uniformly.

[0090] The heat treatment temperature in the nitriding treatment of the alloy particles (hereinafter, nitriding temperature) is preferably 300 to 600° C., particularly preferably 400 to 550° C., and is performed by replacing the atmosphere with a nitrogen atmosphere within this temperature range. The heat treatment time may be set to such an extent that the nitriding of the alloy particles is sufficiently uniform.

[0091] The product obtained after the nitriding step may contain, in addition to the magnetic particles, by-produced CaO, unreacted metallic calcium, etc., which may be in the form of a composite sintered mass. In such a case, the product may be poured into cooling water, and the CaO and metallic calcium may be separated from the magnetic particles as a calcium hydroxide (Ca(OH)2) suspension. Furthermore, the remaining calcium hydroxide may be sufficiently removed by washing the magnetic particles with acetic acid, etc.

[0092] The SmFeN-based anisotropic magnetic powder obtained by the above-mentioned manufacturing method is 17 It has a crystal structure of the type Sm x Fe 100-x-y N y It is a nitride composed of the rare earth metal samarium Sm, iron Fe, and nitrogen N, represented by the formula: Here, it is preferable that x is 8.1 atomic % or more and 10 atomic % or less, y is 13.5 atomic % or more and 13.9 atomic % or less, and the remainder is mainly Fe.

[0093] The average particle size of the SmFeN anisotropic magnetic powder is preferably 2 μm or more and 5 μm or less, more preferably 2.5 μm or more and 4.8 μm or less. If it is less than 2 μm, the filling amount of the magnetic powder in the bonded magnet becomes small, so the magnetization decreases, and if it exceeds 5 μm, the coercive force of the bonded magnet tends to decrease. Here, the average particle size is the particle size measured under dry conditions using a laser diffraction type particle size distribution measuring device.

[0094] The particle size D10 of the SmFeN anisotropic magnetic powder is preferably 1 μm or more and 3 μm or less, and more preferably 1.5 μm or more and 2.5 μm or less. If it is less than 1 μm, the filling amount of the magnetic powder in the bonded magnet becomes small, so the magnetization decreases, while if it exceeds 3 μm, the coercive force of the bonded magnet tends to decrease. Here, D10 is the particle size at which the integrated value of the particle size distribution based on the volume of the SmFeN anisotropic magnetic powder corresponds to 10%.

[0095] The particle size D50 of the SmFeN anisotropic magnetic powder is preferably 2.5 μm or more and 5 μm or less, and more preferably 2.7 μm or more and 4.8 μm or less. If it is less than 2.5 μm, the filling amount of the magnetic powder in the bonded magnet becomes small, so the magnetization decreases, and if it exceeds 5 μm, the coercive force of the bonded magnet tends to decrease. Here, D50 is the particle size at which the integrated value of the particle size distribution based on the volume of the SmFeN anisotropic magnetic powder corresponds to 50%.

[0096] The particle size D90 of the SmFeN anisotropic magnetic powder is preferably 3 μm to 7 μm, more preferably 4 μm to 6 μm. If it is less than 3 μm, the filling amount of the magnetic powder in the bonded magnet is small, so the magnetization decreases, and if it exceeds 7 μm, the coercive force of the bonded magnet tends to decrease. Here, D90 is the particle size at which the integrated value of the particle size distribution based on volume of the SmFeN anisotropic magnetic powder corresponds to 90%.

[0097] The span of the SmFeN anisotropic magnetic powder is defined as follows: Span = (D90-D10) / D50 From the viewpoint of coercive force, is preferably 2 or less, and more preferably 1.5 or less.

[0098] The circularity of the SmFeN anisotropic magnetic powder is not particularly limited, but is preferably 0.5 or more, more preferably 0.6 or more. If it is less than 0.5, the flowability is deteriorated, and stress is applied between particles during molding, resulting in a decrease in magnetic properties. Here, to measure the circularity, an SEM image taken at 3000 times magnification is binarized by image processing, and the circularity is obtained for each particle. The circularity defined in the present invention means the average value of the circularity obtained by measuring about 1000 to 10000 particles. In general, the circularity increases as the number of particles having a smaller particle size increases, so the circularity is measured for particles having a diameter of 1 μm or more. The definition formula: circularity=(4πS / L2) is used to measure the circularity. Here, S is the two-dimensional projected area of ​​the particle, and L is the two-dimensional projected perimeter.

[0099] <Manufacturing method of phosphate-coated SmFeN-based anisotropic magnetic powder> In the first and second methods of manufacturing the bonded magnet compound of the present embodiment, the SmFeN anisotropic magnetic powder contained in the magnetic powder may be a phosphate-coated SmFeN anisotropic magnetic powder. The phosphate-coated SmFeN anisotropic magnetic powder can be produced by adding a pH-adjusted phosphoric acid treatment solution to a slurry containing the SmFeN anisotropic magnetic powder.

[0100] [Phosphating process] In the phosphoric acid treatment process, the SmFeN anisotropic magnetic powder, the solvent, and the phosphoric acid compound are mixed to obtain an SmFeN anisotropic magnetic powder having a surface coated with phosphate. The phosphate-coated SmFeN anisotropic magnetic powder is formed by the reaction of the metal components (e.g., iron and samarium) contained in the SmFeN anisotropic magnetic powder with the phosphoric acid component contained in the phosphoric acid compound, resulting in the precipitation of phosphate (e.g., iron phosphate, samarium phosphate) on the surface of the SmFeN anisotropic magnetic powder. In particular, by using water as the solvent, phosphate with a smaller particle size is precipitated compared to the case where the solvent is an organic solvent, so that a phosphate-coated SmFeN anisotropic magnetic powder with a dense coating is obtained, and the coercive force (iHc) is improved. The case where the solvent is water will be described below.

[0101] In the phosphoric acid treatment step, a slurry containing SmFeN anisotropic magnetic powder, water, and a phosphoric acid compound is prepared. The method of preparing the slurry is not particularly limited, but for example, the slurry is obtained by mixing SmFeN anisotropic magnetic powder and an aqueous phosphoric acid solution containing a phosphoric acid compound using water as a solvent. The content of SmFeN anisotropic magnetic powder in the slurry is, for example, 1% by mass or more and 50% by mass or less, and from the viewpoint of productivity, it is preferable that it is 5% by mass or more and 20% by mass or less. The content of phosphoric acid component (PO4) in the slurry is, for example, 0.01% by mass or more and 10% by mass or less in terms of PO4 conversion, and from the viewpoint of reactivity between metal components and phosphoric acid components and productivity, it is preferable that it is 0.05% by mass or more and 5% by mass or less.

[0102] The phosphoric acid aqueous solution is obtained by mixing a phosphoric acid compound with water. Examples of phosphoric acid compounds include inorganic phosphoric acids such as orthophosphoric acid, sodium dihydrogen phosphate, sodium monohydrogen phosphate, ammonium dihydrogen phosphate, ammonium monohydrogen phosphate, zinc phosphate, and calcium phosphate, inorganic phosphoric acids such as hypophosphorous acid, hypophosphite, pyrophosphoric acid, and polyphosphoric acid, and organic phosphoric acids. These may be used alone or in combination of two or more. In addition, for the purpose of improving the water resistance and corrosion resistance of the coating portion and the magnetic properties of the magnetic powder, oxoacid salts such as molybdate, tungstate, vanadate, and chromate, oxidizing agents such as sodium nitrate and sodium nitrite, and chelating agents such as EDTA can be used as additives.

[0103] The phosphoric acid concentration (PO4 equivalent) in the phosphoric acid aqueous solution is, for example, 5% by mass or more and 50% by mass or less, and preferably 10% by mass or more and 30% by mass or less in terms of the solubility of the phosphoric acid compound, storage stability, and ease of chemical conversion treatment. The pH of the phosphoric acid aqueous solution is, for example, 1 to 4.5, and preferably 1.5 to 4 in terms of ease of controlling the precipitation rate of the phosphate. The pH can be adjusted with dilute hydrochloric acid, dilute sulfuric acid, etc.

[0104] In the phosphoric acid treatment step, it is preferable to add an inorganic acid to adjust the pH of the slurry to 1 or more and 4.5 or less. When the pH is adjusted to 1 or more and 4.5 or less, the amount of phosphate precipitated can be increased compared to the case where the pH is not adjusted, and a phosphate-coated SmFeN-based anisotropic magnetic powder with a thick coating portion can be obtained, which is considered to improve the coercive force (iHc). The pH range to be adjusted is preferably pH 1 or more and 4.5 or less, more preferably pH 1.6 or more and 3.9 or less, and even more preferably pH 2 or more and 3 or less. Examples of inorganic acids to be added include hydrochloric acid, nitric acid, sulfuric acid, boric acid, and hydrofluoric acid. During the phosphoric acid treatment step, inorganic acids are added as needed to achieve the above pH range. Inorganic acids are used from the viewpoint of waste liquid treatment, but organic acids can be used in combination depending on the purpose. Examples of organic acids include acetic acid, formic acid, and tartaric acid.

[0105] In the phosphoric acid treatment step, when the pH of the slurry is adjusted to 1 or more and 4.5 or less by adding inorganic acid, the adjustment is preferably carried out for 10 minutes or more, and more preferably for 30 minutes or more from the viewpoint of reducing the areas where the coating thickness is thin. In the initial stage of pH maintenance, the pH rises quickly so that the intervals between feeding inorganic acid for pH control are short, but as coating progresses, the pH fluctuation gradually becomes gentler and the intervals between feeding inorganic acid become longer, from which the reaction end point can be determined.

[0106] [Oxidation process after phosphoric acid treatment] The phosphate-coated SmFeN anisotropic magnetic powder may be oxidized as necessary. By oxidizing the phosphate-coated SmFeN anisotropic magnetic powder, the surface of the SmFeN anisotropic magnetic powder base material coated with phosphate is oxidized to form an iron oxide layer, improving the oxidation resistance of the phosphate-coated SmFeN anisotropic magnetic powder. In addition, by oxidizing, it is possible to suppress undesirable oxidation-reduction reactions, decomposition reactions, and deterioration on the surface of the SmFeN particles when the phosphate-coated SmFeN anisotropic magnetic powder is exposed to high temperatures during the production of a bonded magnet, and as a result, a magnet with high magnetic properties, especially intrinsic coercivity (iHc), can be obtained.

[0107] The oxidation treatment is carried out by heat treating the SmFeN-based anisotropic magnetic powder after the phosphoric acid treatment in an oxygen-containing atmosphere. The reaction atmosphere preferably contains oxygen in an inert gas such as nitrogen or argon. The oxygen concentration is preferably 3% to 21%, more preferably 3.5% to 10%. During the oxidation reaction, the gas is preferably exchanged at a flow rate of 2 L / min to 10 L / min per 1 kg of magnetic powder.

[0108] The temperature during the oxidation treatment is preferably 150°C or more and 250°C or less, and more preferably 170°C or more and 230°C or less. If the temperature is less than 150°C, the iron oxide layer is not sufficiently formed, and the oxidation resistance tends to be reduced. If the temperature exceeds 250°C, the iron oxide layer is excessively formed, and the coercive force tends to decrease. The reaction time is preferably 3 hours or more and 10 hours or less.

[0109] The SmFeN based anisotropic magnetic powder after the phosphoric acid treatment may be subjected to the above-mentioned silica treatment or silane coupling treatment, if necessary.

[0110] The SmFeN anisotropic magnetic powder after the phosphoric acid treatment step, the oxidation step, the silica treatment, or the silane coupling treatment can be filtered, dehydrated, and dried by a conventional method.

[0111] <Phosphate-coated SmFeN anisotropic magnetic powder> The lower limit of the phosphate content in the phosphate-coated SmFeN-based anisotropic magnetic powder may be 0.1% by mass or more, preferably 0.55% by mass or more, and particularly preferably 0.75% by mass or more, and the upper limit of the phosphate content is preferably 4.5% by mass or less, more preferably 2.5% by mass or less, and particularly preferably 2% by mass or less. If the phosphate content is 0.1% by mass or less, the effect of the phosphate coating tends to be small, and if it exceeds 4.5% by mass, the phosphate-coated SmFeN-based anisotropic magnetic powders tend to aggregate with each other and the coercive force tends to decrease. The phosphate content of the magnetic powder is expressed in terms of PO4 molecules measured using ICP atomic emission spectroscopy (ICP-AES).

[0112] Phosphate-coated SmFeN-based anisotropic magnetic powder may have a heat generation start temperature in DSC of 90°C or more, preferably 120°C or more, more preferably 170°C or more, and particularly preferably 200°C or more. The heat generation start temperature in DSC is a comprehensive evaluation of the denseness, thickness, oxidation resistance, etc. of the phosphate coating, and a high coercive force is obtained when the temperature is 90°C or more. The heat generation start temperature in DSC can be measured, for example, by weighing 20 mg of the phosphate-coated SmFeN-based anisotropic magnetic powder and performing DSC analysis using a high-temperature differential scanning calorimeter (DSC6300, manufactured by Hitachi High-Tech Science Corporation) under the measurement conditions of air atmosphere (200mL / min), room temperature to 400°C (heating rate: 20°C / min), and reference: alumina (20mg). A high heat generation start temperature means that the phosphate coating is formed more densely because heat generation due to oxidation is less likely to occur.

[0113] In the XRD diffraction pattern of the phosphate-coated SmFeN-based anisotropic magnetic powder, the ratio (I) / (II) of the diffraction peak intensity (I) of the (110) plane of αFe to the peak intensity (II) of the (300) plane of the SmFeN-based anisotropic magnetic powder is 3×10 -2 It is preferable that the value is less than 2.5×10 -2 More preferably, it is 1.0×10 -2 The diffraction peak intensity (I) of the (110) plane of αFe represents the amount of αFe present as an impurity, and the above-mentioned ratio (I) / (II) is preferably 2.5×10 or less. -2 A high coercive force can be obtained when the XRD diffraction peak intensity is, for example, measured by measuring the XRD pattern of a phosphate-coated SmFeN-based anisotropic magnetic powder with a powder X-ray crystal diffractometer (manufactured by Rigaku Corporation, X-ray wavelength: CuKa1) and determining the diffraction peak intensity of the (110) plane of α-Fe as SmFe 17 The α-Fe peak height ratio can be calculated by dividing the peak intensity by the peak intensity of the (300) plane of N3. A low α-Fe peak height ratio means a low content of α-Fe, which is an impurity.

[0114] The carbon content of the phosphate-coated SmFeN-based anisotropic magnetic powder is preferably 1000 ppm or less, more preferably 800 ppm or less. The carbon content indicates the amount of organic impurities in the phosphate, and if the carbon content exceeds 1000 ppm, the phosphate-coated SmFeN-based anisotropic magnetic powder is exposed to high temperatures in the process of producing a bonded magnet, which decomposes the organic impurities and causes defects in the coating, tending to reduce the coercive force. Here, the carbon content can be measured by the TOC method.

[0115] The thickness of the phosphate coating portion of the phosphate-coated SmFeN-based anisotropic magnetic powder is not particularly limited, but is preferably 10 nm or more and 200 nm or less in terms of the coercive force of the phosphate-coated SmFeN-based anisotropic magnetic powder. The thickness of the phosphate coating portion can be measured by performing composition analysis by line analysis using EDX on the cross section of the phosphate-coated SmFeN-based anisotropic magnetic powder.

[0116] The NdFeB magnetic powder contained in the magnetic powder may be treated with phosphoric acid, oxidation, silica, or silane coupling as necessary, similar to the SmFeN anisotropic magnetic powder. Each treatment can be performed under the same conditions as the SmFeN anisotropic magnetic powder. EXAMPLES

[0117] The present invention will be specifically described below based on examples, but the present invention is not limited to these examples.

[0118] In the examples and comparative examples, the following materials were used. Epoxy resin: Biphenyl type (epoxy equivalent: 186g / eq) Hardener: DDS (diaminodiphenyl sulfone) (active hydrogen equivalent: 62.0 g / eq) Curing accelerator: TPP (triphenylphosphine) SmFeN anisotropic magnetic powder (Z12P-P1 manufactured by Nichia Corporation, average particle size 3 μm (particle size distribution is monodisperse), residual magnetic flux density of magnetic powder alone Br = 1.32 T, coercive force 948 kA / m) NdFeB anisotropic magnetic powder (MF-18P manufactured by Aichi Steel Corporation, average particle size: 130.5 μm (VMD) D50: 124.9 μm, D90: 211.3 μm, residual magnetic flux density of magnetic powder alone Br = 1.24 T, coercive force 1356 kA / m) Thermoplastic resin: Polyamide 12 (ZZ3000P manufactured by Daicel-Evonik)

[0119] Manufacturing Example 1 (Magnetic powder production) 100 parts by weight of SmFeN magnetic powder was surface-treated with 1.875 parts by weight of ethyl silicate and 0.4 parts by weight of 3-aminopropyltriethoxysilane silane (Z-6011, manufactured by Dow Corning Toray Co., Ltd.) to prepare a surface-treated SmFeN magnetic powder.

[0120] 100 parts by weight of NdFeB magnetic powder was surface-treated with 1.875 parts by weight of ethyl silicate and 0.4 parts by weight of 3-aminopropyltriethoxysilane silane (Z-6011 manufactured by Dow Corning Toray Co., Ltd.) to prepare a surface-treated NdFeB magnetic powder.

[0121] Manufacturing Example 2 (Preparation of additives for bonded magnets) 12 parts by weight of epoxy resin, 8.8 parts by weight of hardener, and 0.4 parts by weight of hardening accelerator were dissolved and mixed in 100 parts by weight of acetone. After volatilizing the acetone, the mixture was hardened in a tray dryer at 200°C for 6 hours under a nitrogen atmosphere. The hardened material obtained was pulverized in a mixer and classified using a sieve with 500μm openings to produce an additive for bonded magnets.

[0122] Production Example 3 (Preparation of resin composition for bonded magnets) 17.4 parts by weight of the additive for bonded magnets obtained in Production Example 2 was melt-kneaded with 100 parts by weight of polyamide 12 in a twin-screw kneader in an environment of 210° C. to obtain a resin composition for bonded magnets.

[0123] Example 1 (Making compounds for bonded magnets) The surface-treated SmFeN anisotropic magnetic powder and the surface-treated NdFeB magnetic powder prepared in Production Example 1 were mixed in a mass ratio of 50:50 (volume ratio of 50.5:49.5). 100 parts by weight of the mixed magnetic powder were mixed with 1.08 parts by weight of the additive for bonded magnets prepared in Production Example 2 and 6.24 parts by weight of polyamide 12, and the mixture was melt-extruded and kneaded in a twin-screw kneader at 210°C to obtain a compound for bonded magnets.

[0124] (Production of bonded magnets) The resulting bonded magnet compound was injection molded at a cylinder temperature of 260° C. and a mold temperature of 90° C. to obtain a bonded magnet with a diameter of 10 mm and a thickness of 7 mm. The injection pressure during injection molding was 51 MPa.

[0125] Example 2 (Making compounds for bonded magnets) The surface-treated SmFeN anisotropic magnetic powder and the surface-treated NdFeB magnetic powder prepared in Production Example 1 were mixed in a mass ratio of 50:50 (volume ratio of 50.5:49.5). 0.91 parts by weight of the additive for bonded magnets prepared in Production Example 2 and 5.29 parts by weight of polyamide 12 were kneaded with 100 parts by weight of the mixed magnetic powder, and the mixture was melt-extruded and kneaded in a twin-screw kneader at 210°C to obtain a compound for bonded magnets.

[0126] (Production of bonded magnets) The resulting bonded magnet compound was used to obtain a bonded magnet in the same manner as in Example 1. The injection pressure during injection molding was 82 MPa.

[0127] Example 3 (Making compounds for bonded magnets) The surface-treated SmFeN anisotropic magnetic powder and the surface-treated NdFeB magnetic powder prepared in Production Example 1 were mixed in a mass ratio of 50:50 (volume ratio of 50.5:49.5). 100 parts by weight of the mixed magnetic powder were mixed with 0.77 parts by weight of the additive for bonded magnets prepared in Production Example 2 and 4.44 parts by weight of polyamide 12, and the mixture was melt-extruded and kneaded in a twin-screw kneader at 210°C to obtain a compound for bonded magnets.

[0128] (Production of bonded magnets) The resulting bonded magnet compound was used to obtain a bonded magnet in the same manner as in Example 1. The injection pressure during injection molding was 143 MPa.

[0129] Example 4 (Making compounds for bonded magnets) The surface-treated SmFeN anisotropic magnetic powder and the surface-treated NdFeB magnetic powder prepared in Production Example 1 were mixed in a mass ratio of 50:50 (volume ratio of 50.5:49.5). 100 parts by weight of the mixed magnetic powder were mixed with 0.57 parts by weight of the additive for bonded magnets prepared in Production Example 2 and 4.18 parts by weight of polyamide 12, and the mixture was melt-extruded and kneaded in a twin-screw kneader at 210°C to obtain a compound for bonded magnets.

[0130] (Production of bonded magnets) The resulting bonded magnet compound was used to obtain a bonded magnet in the same manner as in Example 1. The injection pressure during injection molding was 246 MPa.

[0131] Example 5 (Making compounds for bonded magnets) The surface-treated SmFeN anisotropic magnetic powder and the surface-treated NdFeB magnetic powder prepared in Production Example 1 were mixed in a mass ratio of 50:50 (volume ratio of 50.5:49.5). 7.32 parts by weight of the resin composition for bonded magnets prepared in Production Example 3 was kneaded with 100 parts by weight of the mixed magnetic powder, and melt extrusion kneaded in a twin-screw kneader under a 210°C environment to obtain a compound for bonded magnets.

[0132] (Production of bonded magnets) The resulting bonded magnet compound was used to obtain a bonded magnet in the same manner as in Example 1. The injection pressure during injection molding was 49 MPa.

[0133] Example 6 (Making compounds for bonded magnets) The surface-treated SmFeN anisotropic magnetic powder and the surface-treated NdFeB magnetic powder prepared in Production Example 1 were mixed in a mass ratio of 50:50 (volume ratio of 50.5:49.5). 6.2 parts by weight of the resin composition for bonded magnets prepared in Production Example 3 was kneaded with 100 parts by weight of the mixed magnetic powder, and melt-extrusion kneaded in a twin-screw kneader under a 210°C environment to obtain a compound for bonded magnets.

[0134] (Production of bonded magnets) The resulting bonded magnet compound was used to obtain a bonded magnet in the same manner as in Example 1. The injection pressure during injection molding was 76 MPa.

[0135] Example 7 (Making compounds for bonded magnets) The surface-treated SmFeN anisotropic magnetic powder and the surface-treated NdFeB magnetic powder prepared in Production Example 1 were mixed in a mass ratio of 50:50 (volume ratio of 50.5:49.5). 5.2 parts by weight of the resin composition for bonded magnets prepared in Production Example 3 was kneaded with 100 parts by weight of the mixed magnetic powder, and melt-extrusion kneaded in a twin-screw kneader under a 210°C environment to obtain a compound for bonded magnets.

[0136] (Production of bonded magnets) The resulting bonded magnet compound was used to obtain a bonded magnet in the same manner as in Example 1. The injection pressure during injection molding was 139 MPa.

[0137] Example 8 (Making compounds for bonded magnets) The surface-treated SmFeN anisotropic magnetic powder and the surface-treated NdFeB magnetic powder prepared in Production Example 1 were mixed in a mass ratio of 50:50 (volume ratio of 50.5:49.5). 4.17 parts by weight of the resin composition for bonded magnets prepared in Production Example 3 were kneaded with 100 parts by weight of the mixed magnetic powder, and melt extrusion kneaded in a twin-screw kneader under a 210°C environment to obtain a compound for bonded magnets.

[0138] (Production of bonded magnets) The resulting bonded magnet compound was used to obtain a bonded magnet in the same manner as in Example 1. The injection pressure during injection molding was 238 MPa.

[0139] Comparative Example 1 (Making compounds for bonded magnets) The surface-treated SmFeN anisotropic magnetic powder and the surface-treated NdFeB magnetic powder prepared in Production Example 1 were mixed in a mass ratio of 50:50 (volume ratio of 50.5:49.5). 7.14 parts by weight of polyamide 12 was kneaded with 100 parts by weight of the mixed magnetic powder, and melt extrusion kneaded in a twin-screw kneader under a 210°C environment to obtain a bonded magnet compound.

[0140] (Production of bonded magnets) The resulting bonded magnet compound was used to obtain a bonded magnet in the same manner as in Example 1. The injection pressure during injection molding was 53 MPa.

[0141] Comparative Example 2 (Making compounds for bonded magnets) The surface-treated SmFeN anisotropic magnetic powder and the surface-treated NdFeB magnetic powder prepared in Production Example 1 were mixed in a mass ratio of 50:50 (volume ratio of 50.5:49.5). 6.06 parts by weight of polyamide 12 was kneaded with 100 parts by weight of the mixed magnetic powder, and melt extrusion kneaded in a twin-screw kneader under a 210°C environment to obtain a bonded magnet compound.

[0142] (Production of bonded magnets) The resulting bonded magnet compound was used to obtain a bonded magnet in the same manner as in Example 1. The injection pressure during injection molding was 91 MPa.

[0143] Comparative Example 3 (Making compounds for bonded magnets) The surface-treated SmFeN anisotropic magnetic powder and the surface-treated NdFeB magnetic powder prepared in Production Example 1 were mixed in a mass ratio of 50:50 (volume ratio of 50.5:49.5). 5.08 parts by weight of polyamide 12 was kneaded with 100 parts by weight of the mixed magnetic powder, and melt extrusion kneaded in a twin-screw kneader under a 210°C environment to obtain a bonded magnet compound.

[0144] (Production of bonded magnets) The resulting bonded magnet compound was used to obtain a bonded magnet in the same manner as in Example 1. The injection pressure during injection molding was 153 MPa.

[0145] Comparative Example 4 (Making compounds for bonded magnets) The surface-treated SmFeN anisotropic magnetic powder and the surface-treated NdFeB magnetic powder prepared in Production Example 1 were mixed in a mass ratio of 50:50 (volume ratio of 50.5:49.5). 4.63 parts by weight of polyamide 12 was kneaded with 100 parts by weight of the mixed magnetic powder, and melt extrusion kneaded in a twin-screw kneader under a 210°C environment to obtain a bonded magnet compound.

[0146] (Production of bonded magnets) When the same procedure as in Example 1 was carried out using the resulting bonded magnet compound, the injection mold could not be filled completely, and a molded product could not be obtained.

[0147] The residual magnetic flux density Br, coercive force iHc, and orientation rate of the bonded magnets obtained in the examples and comparative examples were evaluated by the following methods. The evaluation results are shown in Table 1.

[0148] <Residual magnetic flux density, coercive force and orientation rate>

[0149] The residual magnetic flux density Br (T) and coercive force iHc (kA / m) of the produced bonded magnets were measured using a BH tracer. The orientation rate was calculated using the following formula. Orientation rate (%) = Residual magnetic flux density Br (T) measured with a BH tracer / (Residual magnetic flux density Br (T) of SmFeN anisotropic magnetic powder alone × Volume filling rate (vol%) of mixed magnetic powder ÷ 100 × Volume ratio of SmFeN anisotropic magnetic powder ÷ 100 + Residual magnetic flux density Br (T) of NdFeB magnetic powder alone × Volume filling rate (vol%) of mixed magnetic powder ÷ 100 × Volume ratio of NdFeB magnetic powder ÷ 100)

[0150] [Table 1]

[0151] From Table 1, it was confirmed that in the examples, the injection pressure was lower and the flowability of the bonded magnet compound was improved when compared to the comparative examples with the same volumetric filling rate of the magnetic powder. It was also confirmed that the improved flowability of the bonded magnet compound resulted in a higher coercive force in the bonded magnet.

[0152] DSC measurements were performed on polyamide 12, a powder mixture of polyamide 12 and the additive for bonded magnets produced in Production Example 2 in the ratios shown in Table 2 below, and the resin composition for bonded magnets produced in Production Example 3. The DSC measurements were performed using a differential scanning calorimeter by increasing the temperature to 210°C at 10°C / min and then decreasing the temperature to 30°C at 5°C / min. The values ​​of the melting peak and crystallization peak are shown in Table 2.

[0153] [Table 2]

[0154] In the resin composition for bonded magnets, in which the cured material was melt-kneaded with polyamide 12 in advance, the melting point was approximately 5°C lower and the crystallization temperature was approximately 3°C lower than that of polyamide 12 alone. The lower melting point and crystallization temperature slow down the cooling and solidification of the resin in the mold during injection molding, which is presumably improving the fluidity of the compound for bonded magnets. [Industrial Applicability]

[0155] According to the method for producing a compound for a bonded magnet of the present invention, it is possible to obtain a compound for a bonded magnet with greatly improved flowability, and the coercive force of the obtained bonded magnet can also be improved. The obtained bonded magnet can be suitably applied as a composite material and a bonded magnet for use in motors and the like.

Claims

1. A step of thermally curing a thermosetting resin and a curing agent having a ratio of the number of reactive groups to the number of reactive groups of the thermosetting resin of 2 or more and 11 or less to obtain a cured product of the thermosetting resin and the curing agent, which is an additive for a thermoplastic resin-containing bonded magnet; a kneading step of kneading the additive for thermoplastic resin-containing bonded magnets, magnetic powder, and thermoplastic resin to obtain a compound for thermoplastic resin-containing bonded magnets; Including, The magnetic powder includes NdFeB-based magnetic powder and SmFeN-based anisotropic magnetic powder. A method for producing a compound for bonded magnets containing thermoplastic resin.

2. A step of thermally curing a thermosetting resin and a curing agent having a ratio of the number of reactive groups to the number of reactive groups of the thermosetting resin of 2 or more and 11 or less to obtain a cured product of the thermosetting resin and the curing agent, which is an additive for a thermoplastic resin-containing bonded magnet; A step of kneading the additive for thermoplastic resin-containing bonded magnets with a thermoplastic resin to obtain a resin composition for thermoplastic resin-containing bonded magnets; a kneading step of kneading the resin composition for thermoplastic resin-containing bonded magnets and magnetic powder to obtain a compound for thermoplastic resin-containing bonded magnets; Including, The magnetic powder includes NdFeB-based magnetic powder and SmFeN-based anisotropic magnetic powder. A method for producing a compound for bonded magnets containing thermoplastic resin.

3. 3. The method for producing a compound for a bonded magnet containing a thermoplastic resin according to claim 1, wherein the thermoplastic resin is a nylon resin.

4. 4. The method for producing a compound for a thermoplastic resin-containing bonded magnet according to claim 1, wherein the SmFeN-based anisotropic magnetic powder has a monodisperse particle size distribution.

5. A compound for a thermoplastic resin-containing bonded magnet obtained by the manufacturing method according to any one of claims 1 to 4.

6. A step of thermally curing a thermosetting resin and a curing agent having a ratio of the number of reactive groups to the number of reactive groups of the thermosetting resin of 2 or more and 11 or less to obtain a cured product of the thermosetting resin and the curing agent, which is an additive for a thermoplastic resin-containing bonded magnet; a kneading step of kneading the additive for thermoplastic resin-containing bonded magnets, magnetic powder, and thermoplastic resin to obtain a compound for thermoplastic resin-containing bonded magnets; an injection molding step of injection molding the obtained thermoplastic resin-containing bonded magnet compound; Including, The magnetic powder includes NdFeB-based magnetic powder and SmFeN-based anisotropic magnetic powder. A method for manufacturing a thermoplastic resin-containing bonded magnet.

7. A step of thermally curing a thermosetting resin and a curing agent having a ratio of the number of reactive groups to the number of reactive groups of the thermosetting resin of 2 or more and 11 or less to obtain a cured product of the thermosetting resin and the curing agent, which is an additive for a thermoplastic resin-containing bonded magnet; A step of kneading the additive for thermoplastic resin-containing bonded magnets with a thermoplastic resin to obtain a resin composition for thermoplastic resin-containing bonded magnets; a kneading step of kneading the resin composition for thermoplastic resin-containing bonded magnets and magnetic powder to obtain a compound for thermoplastic resin-containing bonded magnets; an injection molding step of injection molding the obtained thermoplastic resin-containing bonded magnet compound; Including, The magnetic powder includes NdFeB-based magnetic powder and SmFeN-based anisotropic magnetic powder. A method for manufacturing a thermoplastic resin-containing bonded magnet.

8. A thermoplastic resin-containing bonded magnet obtained by the manufacturing method according to claim 6 or 7.

Citation Information

Patent Citations

  • Rare-earth bonded magnet and its manufacture

    JP1993152116A

  • Surface treating method of rare earth-iron-nitrogen magnetic powder, and plastic magnet formed of the same

    JP2002008911A

  • Surface treatment method of rare earth-iron-nitrogen magnetic power and plastic magnet formed of the same

    JP2002043109A

  • Manufacturing method of radial anisotropic magnet motor

    JP2006158098A

  • Compound magnetic powder for bond magnet, resin composition for bond magnet, and bond magnet

    JP2007035667A